Dynamic Magma Storage at Near‐Ridge Hot Spots: Evidence From New Galápagos Gravity Data. (5th March 2020) - Cleary, Z.; Schwartz, D. M.; Mittelstaedt, E.; Harpp, K.
Abstract: A morphological dichotomy exists between the active western and older (>1–2.5 Ma) eastern volcanoes of the Galápagos Archipelago. All of the young shield volcanoes in the west have calderas, but none are present on the older volcanoes in the east. This striking difference suggests that there has been a change in volcanic construction and magmatic supply processes, a finding dissimilar to the prevailing Hawaiian model of hot spot evolution. Bouguer anomaly highs (30–50 mGal) consistent with dense cumulate bodies are measured over these calderas. In contrast, we present new gravity data from Santa Cruz and San Cristóbal islands that lack comparable gravity highs. We propose that formation of shallow magma reservoirs and their associated Bouguer anomaly highs were inhibited during evolution of the eastern volcanoes because the proximal Galápagos Spreading Center diverted plume material more efficiently 1–2 Ma when the spreading center was 100 km closer to the plume. The difference in caldera expression between the western and eastern islands may be a surface expression of this process. These results suggest that plume‐ridge interaction may play a first‐order role in the evolution of magmatic plumbing systems of near‐ridge ocean islands, which account for one third of hot spot systems. Plain Language Summary: In the Galápagos Archipelago, a striking dichotomy exists in that volcanic islands in the west have calderas, but those in the east do not. In the Galápagos Archipelago, however, we observe dramatically different volcano shapes and lava chemistry between the younger western and older eastern islands. Our study uses new gravity measurements to investigate differences in the magma plumbing between the eastern and western Galápagos volcanoes and how the plumbing has affected the evolution of surface features. Two of the older, more easterly volcanoes, San Cristóbal and Santa Cruz, lack the gravity highs observed on the western volcanoes, indicating that neither island developed a shallow, dense magma chamber. We propose that this shift in the magmatic system was driven by an increase in the distance between the mantle plume and the nearby mid‐ocean ridge by 100 km at 1–2 Ma, which led to higher magma supply to the younger western volcanoes. The difference in caldera expression between the western and eastern islands may be a surface expression of this process. Our findings suggest that plume‐ridge interaction may play a critical role in the construction of near‐ridge islands, which account for one third of hot spot systems. Key Points: New gravity data on the eastern islands unexpectedly lack Bouguer anomaly highs that are found on the western islands Increases in plume‐ridge distance influenced Galápagos volcano construction and magma focusing in the period since 1–2 Ma Mantle plume‐derived ocean island evolution should be considered thoroughly in the context of plume‐ridge interaction